2014
DOI: 10.1037/a0034778
|View full text |Cite
|
Sign up to set email alerts
|

Rodent ultrasonic communication: Male prosocial 50-kHz ultrasonic vocalizations elicit social approach behavior in female rats (Rattus norvegicus).

Abstract: Rats emit distinct types of ultrasonic vocalizations (USV), which serve as situation-dependent affective signals with important communicative functions. Low-frequency 22-kHz USV typically occur in aversive situations, such as social defeat, whereas high-frequency 50-kHz USV can be observed in appetitive situations, like rough-and-tumble-play in juveniles or mating in adults. The 2 main USV types serve distinct communicative functions and induce call-specific behavioral responses in the receiver. While 22-kHz U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
51
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 48 publications
(152 reference statements)
7
51
1
Order By: Relevance
“…Finally, USV emission by the subject rat in response to playback of 50-kHz USVs can be determined (Avisoft Bioacoustics). By this means, it has been consistently shown that 50-kHz USVs lead to social approach behavior in juvenile and adult male rats (Wöhr and Schwarting, 2007, 2009, 2013Brenes et al, 2016;Seffer et al, 2015) as well as in female rats (Willadsen et al, 2014; Fig. 8.35.2), supporting the notion that they serve an affiliative function as social contact calls.…”
mentioning
confidence: 79%
“…Finally, USV emission by the subject rat in response to playback of 50-kHz USVs can be determined (Avisoft Bioacoustics). By this means, it has been consistently shown that 50-kHz USVs lead to social approach behavior in juvenile and adult male rats (Wöhr and Schwarting, 2007, 2009, 2013Brenes et al, 2016;Seffer et al, 2015) as well as in female rats (Willadsen et al, 2014; Fig. 8.35.2), supporting the notion that they serve an affiliative function as social contact calls.…”
mentioning
confidence: 79%
“…High-frequency calls are produced by juvenile or adult rats during rough-and-tumble play [41], during mating [41][42][43][44], as an expression of reward during voluntary exercise [45], as well as in response to drugs of abuse [46,47], and it is widely accepted today that they reflect a positive affective state [46,48,49]. Consequently, one of their functions appears to be the communication of emotional states to conspecifics [50].…”
Section: Introductionmentioning
confidence: 99%
“…Rats emitting high numbers of tickling-induced 50-kHz USVs have been shown to approach the hand of the tickling experimenter with a short latency period [54]. In addition to conveying information appertaining to affective states, 50-kHz USVs are suggested to fulfil important communicative functions and to be involved in the establishment and maintenance of close social contacts [44,[55][56][57][58]. Rats use low-frequency (22-kHz) alarm calls as a warning to conspecifics of imminent dangers, with a view to promoting a survival-enhancing behavioural strategy in the colony as a whole [59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…Production of 50 kHz calls is associated with mating and other social interactions or the expectation of reward (Burgdorff et al, 2008). Playbacks of 50 kHz calls induce approach behavior in both male and female rats, promoting social contact Willadsen et al, 2014). During the encounter with an unfamiliar estrous female prior to mating, a male's vocalizations can contain call types from both the 22 kHz and 50 kHz call category (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wright et al, 2010;Brudzynski, 2013) that play important roles in their social interactions (e.g. Brudzynski, 2009;Willadsen et al, 2014). The rat model has allowed comprehensive recording of peripheral vocal movements (Riede, 2011).…”
Section: Introductionmentioning
confidence: 99%